Evaluation of safety and efficacy of NexGen – an ultrathin strut and hybrid cell design cobalt-chromium bare metal stent implanted in a real life patient population – the Polish NexGen Registry - Milewski, Krzysztof; Gąsior, Paweł; Samborski, Stefan; Buszman, Piotr P.; Błachut, Aleksandra; Wojtaszczyk, Adam; Młodziankowski, Adam; Mendyk, Artur; Król, Marek; Wojakowski, Wojciech; Buszman, Paweł E. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : Despite the dominance of drug-eluting stents in modern interventional cardiology, there is still a niche for bare metal stents. Aim: The aim of the Polish NexGen registry was to evaluate the safety and efficacy of a new generation cobalt-chromium NexGen stent in a real life patient population. Material and methods : A prospective multi-center registry was conducted in five clinical sites of American Heart of Poland. Three hundred and eighty-three patients who underwent percutaneous coronary intervention (PCI) with NexGen stent implantation were included. Clinical follow-up was performed at 1, 6 and 12 months. Additionally, a group of 42 randomly selected patients underwent control angiography at 6 months (10.96% of study population). The primary endpoint was occurrence of target vessel revascularization (TVR) at 6-month follow-up. Angiographic endpoints included rates of binary restenosis and late lumen loss at 6-month follow-up based on QCA analysis. Multivessel disease was present in more than 70% of patients, and 52.4% of lesions were complex. The main indications for angiography were non-ST elevation acute coronary syndromes (54.8%) and ST elevation myocardial infarction (34.99%). Results : At 6-month follow-up 47 (12.7%) patients reached the primary endpoint of TVR. The composite of major acute cardiac event rates at 30-day and 6- and 12-month follow-up was 6.01% (n = 23), 18.5% (n = 69) and 25.21% (n = 92) respectively. Control angiography performed after 6 months showed in-stent late loss of 0.66 ±0.71 mm and a binary restenosis rate of 16.7%. Conclusions : Our study showed that PCI with the NexGen stent is safe and effective at 6- and 12-month follow-up. Angiographic results showed a satisfactory restenosis rate and low late lumen loss.